2022
DOI: 10.3389/fneur.2022.828642
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Precuneus Function and Residual Dizziness in Patients With Benign Paroxysmal Positional Vertigo

Abstract: ObjectivesThe purpose of this study was to apply the amplitude of the low-frequency fluctuation (ALFF) method to investigate the spontaneous brain activity alterations in patients with residual dizziness (RD) after successful canalith repositioning manoeuvre for benign paroxysmal positional vertigo (BPPV).MethodsAll BPPV patients underwent visual vertigo analog scale (VVAS) evaluations and functional magnetic resonance imaging (fMRI). The ALFF method was used to assess the spontaneous brain activity. Screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(41 reference statements)
4
3
0
Order By: Relevance
“…It was demonstrated that electrical stimulation of the precuneus evoked symptom of vertigo, suggesting that the precuneus was an important brain region in processing vestibular information 51,52 . In the present study, we observed decreased FC between left OP2 and left precuneus in BPPV patients with RD compared to healthy controls; this result was in agreement with a previous resting‐state fMRI study which reported decreased ALFF in the bilateral precuneus in BPPV patients with RD 33 . Our results of decreased FC between left OP2 and left precuneus in BPPV patients with RD might indicate decreased connectivity within the vestibular network.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was demonstrated that electrical stimulation of the precuneus evoked symptom of vertigo, suggesting that the precuneus was an important brain region in processing vestibular information 51,52 . In the present study, we observed decreased FC between left OP2 and left precuneus in BPPV patients with RD compared to healthy controls; this result was in agreement with a previous resting‐state fMRI study which reported decreased ALFF in the bilateral precuneus in BPPV patients with RD 33 . Our results of decreased FC between left OP2 and left precuneus in BPPV patients with RD might indicate decreased connectivity within the vestibular network.…”
Section: Discussionsupporting
confidence: 93%
“…The functional changes in the left AG have been previously observed in patients with chronic unilateral vestibulopathy during rest and in patients with PPPD during stationary emotional stimulation 31,32 . Our study found altered function in AG in BPPV patients with RD, which was consistent with a previous resting‐state fMRI study which reported decreased ALFF in the AG in BPPV patients with RD compared to patients without RD 33 . We also found that the FC between left AG and OP2 was negatively correlated with the duration of BPPV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Functional changes in DMN have been reported in vestibular disorders of VM ( 35 ), VN ( 36 ) and persistent postural perceptual dizziness (PPPD) ( 37 ), indicating that DMN might be involved in vestibular information processing. In BPPV patients with RD, altered functional activities in PCU were observed by a previous resting-state fMRI study, which was consistent with the functional change of IC 1 (PCU) found in this study ( 10 ). The PCU, a key region of pDMN, was reported to be significantly activated during optokinetic stimulation ( 38 ) and visuo-spatial imagery ( 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…The authors reported increased functional activities in bilateral pons and left posterior cerebellar regions in BPPV patients, these results indicated that the functional changes in pons might be related to RD after CRM ( 9 ). In another rs-fMRI study, Fu et al applied fALFF analysis to observe the differences in brain functional activity between RD patients and non-RD patients after CRM, the authors found decreased functional activity in bilateral precuneus in patients with RD compared to patients without RD ( 10 ). The above two studies preliminarily suggested that the occurrence of RD symptoms in BPPV patients might be related to central integration and compensation.…”
Section: Introductionmentioning
confidence: 99%